Factors associated with mechanical ventilation in SARS‐CoV‐2 patients treated with high‐flow nasal cannula oxygen and outcomes. Issue 3 (17th November 2021) - Leroux, Xavier; Schock, Maud; Augereau, Olivier; Lessire, Henry; Bouterra, Charles; Belilita, Lounis; Rerat, Pierre; Alvarez, Antonio; Martinot, Martin; Gerber, Victor
Abstract: Five percent of patients infected with SARS‐CoV‐2 require advanced respiratory support. The high‐flow nasal cannula oxygenotherapy (HFNCO) appears to be effective and safe to reduce the need for mechanical ventilation. However, the factors associated with HFNCO failure as well as the outcomes of patients receiving this noninvasive respiratory strategy remain unclear. Thus, we performed this study to determine factors leading to intubation of SARS‐CoV‐2 patients treated with HFNCO and patients' outcomes. We retrospectively analyzed the medical charts of patients admitted in our ICU center for acute respiratory failure due to SARS‐CoV‐2 infection and who initially benefited from HFNCO, between September 1, 2020, and March 1, 2021. We included all adults patients who received HFNCO and compared two groups: those treated with HFNCO alone and those who failed HFNCO. Patients treated with HFNCO and secondarily limited to the use of mechanical ventilation were excluded from the analysis. Sixty‐nine patients were included, 33 were treated with HFNCO alone and 36 failed HFNCO. We found more patients with shock in the HFNCO failure group ( p = 0.001). The mean IGSII score was higher in the HFNCO failure group ( p < 0.001). The minimum PaO2 /FiO2 was lower in the HFNCO failure group ( p = 0.024). The length of stay in ICU was higher in the HFNCO failure group ( p < 0.001). The mean duration of HFNCO before intubation was 1.77 days. Six‐week mortality was higher in the HFNCO failure group ( p = 0.034). Ten patients had a complication during intubation. The HFNCO leads to reduce the intubation rate, the length of stay in ICU, and the mortality. Determining the factors associated with HFNCO failure is important to avoid complications following late intubation. Highlights: The use of HFNCO avoided the need for intubation in 47.8% of the cases in our study. Patients with HFNCO failure have a lower minimal PaO2/FiO2, more shock, an higher IGSII score and a longer length of stay in ICU. We found greater mortality at six weeks in the HFNCO failure group. We found an high rate of complications following the intubation.